2019
DOI: 10.34133/2019/2389254
|View full text |Cite
|
Sign up to set email alerts
|

Light-Written Reversible 3D Fluorescence and Topography Dual-Pattern with Memory and Self-Healing Abilities

Abstract: To achieve the dynamical dual-pattern with multiplex information of complex topography and 3D fluorescence is challenging yet promising for wide applications ranging from visual bioassays, memory, smart devices to smart display. Here, we develop a convenient, reliable, and versatile method to realize the well-ordered dual-pattern with reversible topography and 3D fluorescence via a light direct-writing approach based on the wrinkle mechanism. By introducing the charge transfer (CT) interaction between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…According to our previous study (Bai et al, 2019), the patterns can be written on the surface as shown in Figure 1. In detail, The SBS-An was dissolved in toluene, and the solution was cast on the glass plate.…”
Section: Preparation Of the Surface Patternsmentioning
confidence: 99%
“…According to our previous study (Bai et al, 2019), the patterns can be written on the surface as shown in Figure 1. In detail, The SBS-An was dissolved in toluene, and the solution was cast on the glass plate.…”
Section: Preparation Of the Surface Patternsmentioning
confidence: 99%
“…Tunable luminescent materials, especially organic photoluminescent materials with stimuli-responsive emission properties, have been highlighted as an exciting research topic in the past few decades owing to their prominent potential with regard to light-emitting diodes, [ 1 ] optoelectronic devices, [ 2 ] fluorescent sensing, [ 3 ] in vivo imaging, [ 4 ] anti-counterfeiting, [ 5 ] data storage [ 6 ] and information encryption [ 7 ]. However, applications of tunable fluorescent materials in solid states have been largely hampered because these luminescent systems generally require time-consuming organic synthesis procedures and suffer from reduced photoluminescence (PL) and poor dispersity in solution phases.…”
Section: Introductionmentioning
confidence: 99%
“…The liquid crystal thermodynamic properties also limit the arrangement of periodic structures and consequently the diversity of the diffraction pattern. ,,, Generally, they cannot be designed top-down. In addition, the variation of dynamic diffraction patterns such as the width or field of view is not sufficient. ,,, Besides liquid crystals, surface micro/nanoscale wrinkles, which are often found in bilayer systems, provide an alternative for diffraction gratings. ,, With photomasks, various wrinkled patterns can be designed, and they exhibit diverse diffraction patterns. , Furthermore, dynamic wrinkles are obtained by regulating the modulus of the film or the strain in the bilayer system according to linear buckling theory. Although there are few systematic studies and challenges for dynamic wrinkle-based gratings, these dynamic wrinkles may still find potential application in DDGs. Besides, state-of-the-art wrinkles are all single-sided, which is difficult for realizing complex two-dimensional (2D) diffraction patterns.…”
Section: Introductionmentioning
confidence: 99%